Métodos utilizados ao longo da história para resolver equações quadráticas: para além da fórmula de bháskara - Farias, Bruno de Souza Ribeiro (2016)
The present work of course completion aims to conduct a study on the historical development of the Quadratic Equation. To reach our goal we bring as a methodology the bibliographical research, with a qualitative approach. Reflecting on the difficulties of algebra teaching, we seek to emphasize the teaching of Quadratic Equation through the methodological resource of the History of Mathematics. In order to arrive at the conclusion of our research, we divided the theoretical part of our work into two stages, namely, in the first one, we searched for theoretical references Such as Gutierre (2003), Miguel (2008), Dias (2009), Mizukami (1986), Mendes, (2009) working with Mathematics teaching using the History of Mathematics as a methodological resource as well as some official documents, Curriculum of Paraíba (PARAÍBA, 2010), PCN (BRAZIL, 1998), OCEM (BRAZIL, 2006) and produced one of our chapters. In a second step, we produced a chapter based on the theoretical reference on the historical Of the researchers Baumgart (1992), Boyer (2010), Pintombeira (2004), Dias (2009, p.38), Contador (2008), Gil (2001) and Eves (2004). In a second stage we produced a chapter based on the theoretical framework Equation, culminating in the production of four teaching activities that work with the History of Mathematics involving the Babylonian, Greek, Arab and Hindu civilizations. It may be a proposition for math teachers to approach this content in the classroom.